Guidelines for the planning and implementation of pharmacovigilance systems audit - S. V. Glagolev; Yu. V. Olefir; B. K. Romanov; R. N. Alyautdin (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
General recommendations for planning and implementing of a risk-based approach to audits of pharmacovigilance systems of Marketing Authorisation Holders are presented. A review of the general requirements for audits and audit reporting is given. The role of the pharmacovigilance system master file in the planning of audits and inspections is discussed. The article contains practical recommendations for the Qualified Person Responsible for Pharmacovigilance in Marketing Authorisation Holders.